Does plant variety intellectual property protection improve farm productivity? evidence from cotton varieties - Naseem, Anwar; Oehmke, James F.; Schimmelpfenning, David E. (2005)
The plant variety protection (PVP) system has been criticized by some authors as being nothing more than a marketing tool and not having much effect on productivity. We investigate this issue for the case of cotton in the United States, first by examining trends in cotton varieties planted and then by quantifying the effect of PVP varieties on cotton yields. Our analysis suggests that PVP has led to the development of more varieties and that these varieties have had an overall positive impact of PVP on cotton yields.